20th international conference on dependability and quality management ICDQM-2017 (proceedings review) - Pokorni, Slavko J. (Vojnotehnički glasnik / Military Technical Courier, 2017)
The article presents the basic information about the overal results, significance, international programme committee and working areas of the 20th DQM International Conference on Dependability and Quality Management ICDQM 2017 (papers printed in Serbian) and 8th DQM International Conference on Life Cycle Engineering and Management (papers printed in English and Russian), which was held under the same acronym ICDQM-2017. The number and structure of papers of both conferences are given in Sections: Military Engineering, Quality Engineering, Reliability Engineering, Industrial Engineering, Systems Engineering, Energy Efficiency and Lean Production, as well as a review of the plenary papers presented by the participants from the Armed Forces and the Ministry of Defense of the Republic of Serbia. This year’s Conference has fewer papers from pаrticipants from the Armed Forces and the Ministry of Defense of the Republic of Serbia compared to the previous conference, but with more papers writen in English language.
Keywords: quality; reliability; military engineering; conference; review